Bio-derived epoxy thermosets incorporating imine linkages: Towards sustainable and advanced polymer materials - Dinu, Roxana; Pidvorotnia, Anastasiia; Swanson, David D.; Mija, Alice (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•Synthesis of Schiff-based epoxy thermosets based on natural resources.•Robust crosslinked structures through self-polymerization.•Increased biobased carbon aromatic content through the addition of naringenin.•Bioresins with chemical decomposition ability and thermo-mechanical reprocessing. In the search for sustainable and eco-friendly alternatives, Schiff-based epoxy thermosets are emerging as a promising strategy due to the inherent dynamic and reversible nature of their imine functional groups, which enables thermal reprocessability and chemical recyclability. This article explores the synthesis of Schiff-based epoxy thermosets using sustainable approaches. Starting from vanillin or syringaldehyde, the synthesis involves the incorporation of imine linkages into the epoxy network. A new strategy has been employed by self-polymerization without the use of additional curing agents. This approach conducts to novel thermosets with superior material properties that exceed those reported in previous studies. Thermo-mechanical investigations showed that the designed thermosets have high mechanical properties, with storage moduli at room temperature ranging between 1.5–2.2 GPa, and glass transition values between 138 and 249 °C. Thermal analyses allowed to evaluate the Limit Oxygen Index (LOI) which ranged from 33 % to 36 %, demonstrating excellent flame-retardant properties without the addition of supplementary additives. Their reduced density (0.74–1.09 g/cm3) makes them suitable for applications where weight considerations are critical. These results obtained results place the designed Schiff-based materials as promising candidates for a wide range of high-end applications, particularly in industries that prioritize eco-friendly processes and materials.